2022
DOI: 10.55486/amrrcg.v26i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing Big Issues in Covid-World Accounting Research

Abstract: Reflecting on the third year of the global Covid-19 pandemic, this paper addresses critical issues in the accounting research agenda. Departing from the current vogue for structured and systematic literature reviews, it specifically targets a number of major accountability issues whose importance will be reinforced by the institutional, economic, political and social environment. Informed by a renewed call to address the accounting research-practice gap, the paper examines the increasing importance of public s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 91 publications
0
5
0
2
Order By: Relevance
“…Within academia there has been a growing movement to redefine what accounting is, what it should be, and what should be taught, as reflected in previous articles in this journal, especially McPhail (2022), Troshani (2022), andSangster (2022). Together they reflect upon tensions and divisions within universities researching and teaching accounting on their relationship to accounting professional institutions, especially regarding course content.…”
Section: Introductionmentioning
confidence: 97%
“…Within academia there has been a growing movement to redefine what accounting is, what it should be, and what should be taught, as reflected in previous articles in this journal, especially McPhail (2022), Troshani (2022), andSangster (2022). Together they reflect upon tensions and divisions within universities researching and teaching accounting on their relationship to accounting professional institutions, especially regarding course content.…”
Section: Introductionmentioning
confidence: 97%
“…Dito isso, gostaria de focar no futuro. Para o futuro da pesquisa contábil no Brasil vislumbro que os pesquisadores irão buscar responder aos constantes e revigorados 'chamados' para reduzir a lacuna/distanciamento entre a pesquisa e a prática contábil (Broedel & Flores, 2021;Parker & Troshani, 2022). O distanciamento da pesquisa em contabilidade com a prática contábil tem sido observado há muito tempo e se estende por muitas décadas, tanto no Brasil (Guerreiro, 2022), como internacionalmente (Rajgopal, 2021).…”
unclassified
“…O distanciamento da pesquisa em contabilidade com a prática contábil tem sido observado há muito tempo e se estende por muitas décadas, tanto no Brasil (Guerreiro, 2022), como internacionalmente (Rajgopal, 2021). São vários os fatores que contribuem para essa lacuna, os quais incluem a falta de relevância prática dos achados das pesquisas; falhas de comunicação por parte dos pesquisadores; declínio da interação entre profissionais e pesquisadores; diferenças entre os horizontes de tempo do pesquisador e dos profissionais, o foco dos periódicos acadêmicos em rankings e nos sistemas de avaliação de desempenho das universidades; as diversas e divergentes necessidades de várias partes interessadas; a preferência dos profissionais por formatos de comunicação de revistas/ relatórios/podcasts profissionais/técnicos; e grandes diferenças entre os tópicos pesquisados e as preocupações dos práticos e da sociedade em geral (Parker & Troshani, 2022).…”
unclassified
“…That said, I would like to focus on the future. For the future of accounting research in Brazil I prospect that researchers will seek to respond to the constant and invigorated 'calls' to reduce the gap between research and accounting practice (Broedel & Flores, 2021;Parker & Troshani, 2022). The gap between accounting research and accounting practice has been observed for a long time and extends for many decades, both in Brazil (Guerreiro, 2022) and internationally (Rajgopal, 2021).…”
mentioning
confidence: 99%
“…The gap between accounting research and accounting practice has been observed for a long time and extends for many decades, both in Brazil (Guerreiro, 2022) and internationally (Rajgopal, 2021). There are several factors that contribute to this gap, which include the lack of practical relevance of research findings; failures of communication by researchers; decline of interaction between professionals and researchers; differences between the time horizons of researcher and professionals, the focus of academic journals on rankings and the performance evaluation systems of universities; the diverse and divergent needs of various stakeholders; the preference of professionals for professional/technical journals/reports/podcasts; and great differences between the topics researched and the concerns of the practitioners and society in general (Parker & Troshani, 2022).…”
mentioning
confidence: 99%